Gryllofulvius gibbosus Taszakowski gen. et sp. nov. – a remarkable, flightless and stridulating plant bug (Heteroptera: Miridae: Cylapinae) from Madagascar - Artur Taszakowski; Zdeněk Jindra; †Andrzej Wolski (European Journal of Taxonomy)
Gryllofulvius Taszakowski gen. nov., a new remarkable genus of the subfamily Cylapinae, tribe Fulviini, is described from Madagascar. The new species Gryllofulvius gibbosus Taszakowski gen. et sp. nov. is documented with photographic images, SEM micrographs of the selected body parts, and female genitalic structures. The stridulatory device (embolial stridulitrum and metafemoral plectra) of the new taxon is described, and the stridulation in Cylapinae is discussed.